2008
DOI: 10.1542/peds.2007-2254
|View full text |Cite
|
Sign up to set email alerts
|

Care Coordination for Children and Youth With Special Health Care Needs: A Descriptive, Multisite Study of Activities, Personnel Costs, and Outcomes

Abstract: Care-coordination activity was assessed at the practice level, and the care-coordination measurement tool was used successfully during the operations of typical, pediatric, primary care settings. The presence of acute, family-based social stressors was a significant driver of need for care-coordination activities. A high proportion of dependence on care-coordination performed by physicians led to increased costs. Office-based nurses providing care coordination were responsible for a significant number of episo… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

5
114
2

Year Published

2010
2010
2023
2023

Publication Types

Select...
5
3

Relationship

1
7

Authors

Journals

citations
Cited by 155 publications
(121 citation statements)
references
References 9 publications
5
114
2
Order By: Relevance
“…21 Recent study results have suggested that it is possible to provide coordinated care in primary care settings, often most efficiently performed by nonphysicians, primarily nurses. 22 For example, care coordination would be improved if all pediatricians provided a standing order to hospitals with whom they work that specified that all of his or her patients should receive newborn hearing screening and that the results should be reported to his or her office. The pediatrician's office staff then knows to check all infants for screening results, report those that are missing, and refer newborns who require further evaluation for audiology diagnosis.…”
Section: Ensure That All Infants Have a Medical Home With Adequate Camentioning
confidence: 99%
“…21 Recent study results have suggested that it is possible to provide coordinated care in primary care settings, often most efficiently performed by nonphysicians, primarily nurses. 22 For example, care coordination would be improved if all pediatricians provided a standing order to hospitals with whom they work that specified that all of his or her patients should receive newborn hearing screening and that the results should be reported to his or her office. The pediatrician's office staff then knows to check all infants for screening results, report those that are missing, and refer newborns who require further evaluation for audiology diagnosis.…”
Section: Ensure That All Infants Have a Medical Home With Adequate Camentioning
confidence: 99%
“…We need to develop more robust prospective methods of identifying these children, potentially coupling diagnoses with more noncategorical characteristics, such as technology assistance and/or number of providers. Prospective identification coupled with effectiveness studies may improve our ability to care for these children in hospitals, with tools such as targeted medication reconciliation, 31 family-centered care, 32 teams of integrated providers in outpatient [27][28][29]33 and inpatient settings, 32 care pathways, 34 or portable medical records. 35 Finally, evidence to guide the provision of optimal inpatient health care for medically complex children remains very limited.…”
Section: Discussionmentioning
confidence: 99%
“…For example, the Institute of Medicine has prioritized evaluation of the medical home model for this population of children. [26][27][28][29] At the individual patient level, inpatient systems of care for medically complex children also need to be optimized. These fragile children are more vulnerable to safety issues in the inpatient setting.…”
Section: Nih-pa Author Manuscriptmentioning
confidence: 99%
See 1 more Smart Citation
“…Substantial effort must be directed toward coordinating care across settings to integrate services centered on the comprehensive needs of patients/ families 13 and measuring performance of care-coordination activities. 15 …”
mentioning
confidence: 99%